Unilateral biportal endoscopy for the treatment of adjacent segment disease after lumbar fusion in elderly patients: a matched comparison study - Duan, Hongwei; Liang, Minghui; Xi, Yu; Chen, Ruiyuan; Fan, Ning; Wang, Tianyi; Wang, Aobo; Ma, Ziqian; Zang, Lei; Yuan, Shuo (Frontiers in Surgery, 2025)
BackgroundUnilateral biportal endoscopy (UBE) is an important minimally invasive surgical treatment option for lumbar spinal stenosis (LSS). However, to our knowledge, no studies have focused on UBE for treating adjacent segment disease (ASD) after lumbar fusion. Thus, this study aimed to analyze the clinical efficacy of UBE for ASD patients, and further compare it with non-ASD patients.MethodsThis retrospective study enrolled consecutive patients who underwent UBE decompression surgery for LSS between January 2022 and March 2024. According to the inclusion and exclusion criteria, 82 patients were divided into study group (42 ASD patients) and control group (42 non-ASD patients matched by sex, surgical level, and age). Surgical outcomes were evaluated using the visual analog scale (VAS) and Oswestry Disability Index (ODI) obtained preoperatively, 3 days postoperatively, and at 3- and 12-month follow-ups, along with the MacNab criteria, cross-sectional area of the dural sac, and incidence of complications.ResultsThe ASD and non-ASD groups enrolled 42 patients each. Except for the operative time (P < 0.001), no significant differences in baseline characteristics were observed between the two groups. Both groups showed significant improvement in VAS scores, ODI scores, and dural sac cross-sectional area after UBE surgery (P < 0.001), with sustained clinical efficacy throughout the follow-up period. Although the ASD group had significantly higher preoperative VAS scores for back pain than the non-ASD group (4.78 ± 1.41 vs. 4.02 ± 1.65, P = 0.027), no significant differences were found between the groups at any postoperative follow-up (3 days, 3 months, or 12 months). Based on the MacNab criteria, excellent or good outcomes were observed in 85.7% (36/42) of the patients in the ASD group and 88.1% (37/42) in the non-ASD group, with no significant difference. The incidence of complications was comparable between the two groups (P = 1.000), and no severe complications were observed.ConclusionUBE demonstrated favorable clinical outcomes and safety in treating ASD patients. It may represent a promising minimally invasive option for elderly patients with multiple comorbidities who cannot tolerate revision surgery.